Characterization of Bovine Bone Marrow Derived Mesenchymal Stem Cells and Immunostaining of Differentiated Neurospheres - Dikmen, T; Özden Akkaya, Ö; Nawaz, S; Erdoğan, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Stem cell differentiation has been a key element for the therapeutical applications for various cases. The novel anti-inflammatory and angiogenic findings and potential applications for both autologous and allogenic studies have emphasized about the usage of mesenchymal stem cells in the clinical trials. The neurosphere differentiation studies and their role for peripheral nerve injuries have gained momentum. Following study emphasized on the isolation of stem cells from bovine bone marrow, their characterization by PCR and their differentiation into mesodermal lineages and into neurospheres under specific induction media. The generated neurospheres were durther investigated for their potential expressions of neuroprogenitor markers Sox2, Nestin and neurofilament protein β-III Tubulin by immunofluorescence staining. The results of following study highlight the use of bone marrow derived mesenchymal stem cells for translational research and regenerative therapy.